Characterization of the interfacial interaction of PCC nano powder with tallow fatty acids for HDPE compounding - Chernet Merkneh; Getinet Asrat Mengesha; Shimelis Lemma; Gebisa Bekele (Results in Materials)
Mugar Precipitated Calcium Carbonate (MPCC) Nano-Powders were synthesized using a solution approach and coated with tallow fatty acid to enhance their compatibility with high-density polyethylene (HDPE) composites. The coated MPCC (MCPCC) nanoparticles were incorporated into HDPE to improve interfacial interaction, tensile strength, and toughness. The study investigated the effects of varying MPCC weight percentages (0–40 %) and the role of the tallow fatty acid coating in optimizing composite properties. Thermal, structural, and morphological analyses, including TGA, XRD, FTIR, DLS, and SEM, were conducted to evaluate the dispersion and interfacial interactions between MPCC and the HDPE matrix. The results demonstrated that the tallow coating significantly improved the mechanical properties of the composites. Notably, the coated MPCC nanoparticles enhanced tensile strength and toughness compared to uncoated counterparts, with the coating also contributing to better thermal stability. The research highlights the innovative use of tallow fatty acid as a coating agent to improve filler-matrix compatibility, a distinction from previous studies that often rely on synthetic or non-biodegradable coatings. This approach not only enhances the mechanical and thermal properties of HDPE composites but also offers a sustainable alternative for industrial applications. Further optimization of coating processes and particle size distribution could lead to even greater improvements in composite performance.